The Role And Significance Of Integrated Marketing Concept In Expanding The Share Of Uzbekistan In Global Tourism Markets - Khudoyarov Anvar Aidjanovich (Genius Journals, 2023)
In this article, in order to ensure the effective operation of the tourism industry in the world economy, the fierce competition in the tourism market in Uzbekistan, suggestions have been developed on the active use of the elements of the integrated marketing strategy in the field.
Keywords: Marketing strategy; concept; integration; tourism